HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN HARGA DIRI PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD DR. KANUJOSO DJATIWIBOWO BALIKPAPAN - Thomas Ari Wibowo (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background : Medical records in Dr. Kanujoso Djatiwibowo Hospital is know that, the amount of chronic kidney disease (CKD) is 110 people, and it has been increasing for each year. 4 people showed abashed/unconfident response if thet had to do dialysis and their activities tend to pull themselves away from people around them, when the dialysis time these 4 people were accompanied by their family while 2 people said it was just a regular thing because they did dialysis often and were not accompanied by their family. From interviewed these 6 people, it was not bothering their dietery pattern and sleep pattern.Objective : To discover the correlation between family support with cronic renal disease patient’s pride who runs hemodialysis at Dr. Kanujoso Djatiwibowo Balikpapan in 2017Research Methodology : The design in this research is descriptive correlational, using cross sectional approach. Sample picking uses purposive sampling with the amount of responden is 110. The analyze that has been used is univariat analyze which are responden’s characteristics, family’s supports, and CKD patient’s pride. Bivariat analyze was using rank spearman. Research Result : According to 52 people, the total sample of chronic kidney disease, is gotten the result of frequency distribution based on the age between 40-59, there are 39 people (75%). Most of respondens men with the total 27 people (51,9%). Most of last education are senior high school with the total 30 people (57,7%). Most of jobs are enterpreneurs with the total 21 people (40,4%). The most longest HD more than 2 years are 22 people (42,3%). According to good family supports, there are 45 people (86,5%) and according to high pride, there are 52 people (100%). The result of rank spearman test is gotten p value 0,040 and rxy 0,285.Suggestion : There is a significant correlation between family support with the patient’s pride of chronic kidney disease who runs hemodialysis in Dr Kanujoso Djatiwibowo Balikpapan Hospital.